2015
DOI: 10.1016/j.envres.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to air pollution and type 1 diabetes – Accounting for genetic factors

Abstract: Maternal exposure to air pollution and type 1 diabetes -Accounting for genetic factors. Link to publication Citation for published version (APA): Malmqvist, E., Larsson, H., Jönsson, I., Rignell-Hydbom, A., Ivarsson, S., Tinnerberg, H., ... Rylander, L. (2015). Maternal exposure to air pollution and type 1 diabetes -Accounting for genetic factors. Environmental Research, 140, 268-274. DOI: 10.1016/j.envres.2015 General rights Copyright and moral rights for the publications made accessible in the public portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 29 publications
(28 reference statements)
0
38
0
1
Order By: Relevance
“…In line with this observation, associations between air pollution exposures at the place of residence and liver enzymes have also been observed [106]. Immunomodulatory effects of outdoor air pollution are further hypothesised to promote an earlier onset of type 1 diabetes [107, 108]. Clearly, development of these systemic/metabolic outcomes would be considered adverse, as per consideration 2 (persistence) in table 1; however, their associations with air pollution are not sufficiently robust at this time to consider them to be adverse effects of air pollution.…”
Section: Emerging Adverse Effects Of Outdoor Air Pollutionmentioning
confidence: 86%
“…In line with this observation, associations between air pollution exposures at the place of residence and liver enzymes have also been observed [106]. Immunomodulatory effects of outdoor air pollution are further hypothesised to promote an earlier onset of type 1 diabetes [107, 108]. Clearly, development of these systemic/metabolic outcomes would be considered adverse, as per consideration 2 (persistence) in table 1; however, their associations with air pollution are not sufficiently robust at this time to consider them to be adverse effects of air pollution.…”
Section: Emerging Adverse Effects Of Outdoor Air Pollutionmentioning
confidence: 86%
“…More importantly, our data show no peripheral insulin resistance in the muscle or liver after ozone exposure. Incidentally, exposure to ozone has been associated with TID in pregnancy and in children (Hathout et al, 2002, 2006; Beyerlein et al, 2015; Malmqvist et al, 2015). Our data show that insulin resistance is not the cause of ozone-induced hyperglycemia, glucose intolerance, or the activation of gluconeogenesis observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prenatal exposure to even low levels of air pollution in Sweden were positively associated with T1DM development in children,9 while exposure to nitrate and nitrite may be diabetogenic only at higher levels of exposure 6. Most experimental studies on EDCs and T1DM thus far involve higher doses, but some low dose studies also show harmful effects.…”
Section: Resultsmentioning
confidence: 99%
“…It found that the children of mothers who lived at residences with higher levels of air pollution (nitrogen oxides [NO x ] and ozone) had a higher risk of developing T1DM by 8–14 years of age 9. For NO x , the association was significant for third trimester exposures, and for ozone, for second trimester exposures.…”
Section: Air Pollutionmentioning
confidence: 99%